Edutainment in Qur'an Publishing: Integrating Learning Theories and Entertainment in Indonesian Mushaf - Fatchiatuzahro, Fatchiatuzahro; Imronudin, Imronudin; Reza, Riza Muhammad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2024)
The publication of Qur'an in Indonesia reflects the direction of the publishing industry, which emphasizes products that are not only informative but also interesting and entertaining for readers. This phenomenon was triggered by a response to society's need for access to additional, more complete information. However, innovations like color tajwid have sparked controversy. Further research into the publication of the Qur'an in Indonesia is necessary to fully understand its impact. This study, employing the concept of edutainment, examines how Al-Qur'an manuscripts in Indonesia integrate learning theories and edutainment approaches. Utilizing analytical descriptive methods alongside philosophical-speculative and phenomenological approaches, fifteen manuscripts were analyzed. These manuscripts effectively meet readers' needs while incorporating educational theories and edutainment strategies. Additionally, there is an emphasis on technological innovation, particularly in visual learning methods that utilize both technological and non-technological features. Despite these advancements, the teacher's role remains crucial in promoting independent learning, especially within the context of Qur'an study.